Norms for copulas - William F. Darsow; Elwood T. Olsen (International Journal of Mathematics and Mathematical Sciences)
We consider several norms on the span of the set C of all copulas. Dominance and equivalence relationships among the norms are discussed, and completeness issues are addressed. The motivation for the study is discussed. Applications to the study of one parameter semigroups of copulas are also addressed.